Karakteristik Kajian Islam Kontemporer: Dialektika Barat dan Timur - Amirudin Amirudin; Masayu Mashita Maisarah (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2020)
Islam is understood in multi-meaning, as a religious teaching and as a scientific field. This matter is still being debated by several groups, especially regarding the issue surrounding studying Islam in the West. The purpose of this paper is to examine the development of Islamic studies from time to time. The issue of using a normative and historical approach in Islamic studies has been widely discussed by experts, both from the West and the East. However, in its development, Islamic studies form a separate 'stronghold' with their respective identities in an effort to understand Islamic teachings, both as an 'observer' and as an 'actor' who has an element of partiality. By using a historical approach, this paper will prove the flexibility of Islamic studies, where each